2018
DOI: 10.3390/md16110431
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for Targets of Alien Metabolites: A Novel Peroxisome Proliferator-Activated Receptor (PPAR) Agonist from a Marine Pest

Abstract: Although the chemical warfare between invasive and native species has become a central problem in invasion biology, the molecular mechanisms by which bioactive metabolites from invasive pests influence local communities remain poorly characterized. This study demonstrates that the alkaloid caulerpin (CAU)—a bioactive component of the green alga Caulerpa cylindracea that has invaded the entire Mediterranean basin—is an agonist of peroxisome proliferator-activated receptors (PPARs). Our interdisciplinary study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…Although algal metabolites show structural diversity and redundancy, the mentioned databases could still be available for network pharmacology to get insight into the disease-modifying mechanisms. Following this in silico approach, Vitale et al identified caulerpin as a PPAR agonist which was confirmed by both in vitro and in vivo assays [ 247 ]. In a reverse way, virtual screening through molecular docking analysis could be an alternative to find out potent hits from a large chemical library for a single target.…”
Section: Algal Metabolites-based Drug Discovery and Designmentioning
confidence: 99%
“…Although algal metabolites show structural diversity and redundancy, the mentioned databases could still be available for network pharmacology to get insight into the disease-modifying mechanisms. Following this in silico approach, Vitale et al identified caulerpin as a PPAR agonist which was confirmed by both in vitro and in vivo assays [ 247 ]. In a reverse way, virtual screening through molecular docking analysis could be an alternative to find out potent hits from a large chemical library for a single target.…”
Section: Algal Metabolites-based Drug Discovery and Designmentioning
confidence: 99%
“…Due to its role in adipocyte differentiation, lipid metabolism, glucose homeostasis, insulin sensitivity, and, more recently, in inflammatory and immune responses, PPARγ represents an attractive pharmacological target to address metabolic disorders. As part of our discovery program on nuclear receptor ligands from marine [24,25] and terrestrial sources [15], we focused on cannabimovone (CBM), a polar pCB characterized by a unique abeo-menthane terpenyl moiety isolated in 2010 from a non-psychotropic variety of C. sativa (Italian cultivar Carmagnola) [17]. The chemical structure of cannabimovone, including stereochemical details, was recently confirmed by total synthesis, which can also be considered as an alternative to the exploitation of the natural source [26].…”
Section: Discussionmentioning
confidence: 99%
“…The prediction has been then validated by in vitro assays, coupled with in vivo, ex vivo, and in vitro transcriptional analysis of PPARα downstream genes related to fatty acid hepatic β-oxidation. Overall, the obtained results disclosed the unprecedented molecular interaction of 2 with PPARs, likely to exert cascade effects at all levels of biological organization, down to sea-based economy, with implications of interest for the development of functional foods for human nutrition and/or drugs for treating human chronic diseases [51].…”
mentioning
confidence: 86%
“…In order to characterize the molecular interactions between bioactive metabolites from C. cylindracea that are responsible for the most relevant observed metabolic and behavioral effects, an interdisciplinary study has been carried out starting from in silico studies that led to predict the interaction of 2 with peroxisome proliferator activated receptors (PPARs) [51]. These nuclear receptors play essential roles in the regulation of metabolism and social behavior in vertebrates, mediating the effects of several nutrients and drugs through transcriptional regulation of their target genes.…”
mentioning
confidence: 99%